An in situ formed Se/CMK-3 composite for rechargeable lithium-ion batteries with long-term cycling performance. Issue 35 (22nd August 2016) - Zheng, Cheng; Liu, Minying; Chen, Wenqiang; Zeng, Lingxing; Wei, Mingdeng
Abstract : A Se/CMK-3 composite was in situ synthesized, exhibiting large capacity, high rate performance and excellent long-term cycling stability for Li-ion intercalation. Abstract : A composite of Se/CMK-3 was in situ synthesized for the first time via a carbon thermal reduction route by using ordered mesoporous carbon CMK-3 as a nanoreactor and reduction agent, and was then applied as an anode material for Li-ion intercalation. Owing to the fact that CMK-3 acts as a stable matrix for Se and facilitates electronic conductivity and ion transportation, the composite exhibited large reversible capacity, high rate performance and excellent long-term cycling stability. For instance, a reversible capacity of 770 mA h g −1 can be achieved after 100 cycles at 1C, and a capacity of 619 mA h g −1 was retained after 1000 cycles even at a rate as high as 2C.